PTH-133 Five years of HIFIVE (human factors in virtual endoscopy): an endoscopic non-technical skills simulation programme. (8th June 2018) - Menabawey, Tareq El; Dimmock, Valerie; Gadock, Radha; Murray, Sam; Ravindran, Vathsan; Wood, Eleanor
Abstract : Introduction: Endoscopic non-technical skills (ENTS) are increasingly recognised as a vital component of endoscopic ability. The Joint Advisory Group on GI endoscopy (JAG) have included them in their updated direct observation of procedural skills (DOPS) assessments of endoscopy competency and therefore competence in these skills is required for accreditation. However, a formal framework for teaching these skills has not yet been established. Here we describe our centre's five year experience of running a one-day multidisciplinary immersive simulation course aimed at developing ENTS matched to the JAG curriculum. Methods: From 2012–17, we have run 8 simulation days involving 5 standardised scenarios based on real life serious incidents, using simulated patients, an endoscopy simulator (GI Mentor Express Symbionix) and vital signs consoles (iSimulate). Doctors, nurses and healthcare assistants from endoscopy units attended. From 2012–16 post course questionnaires were completed by attendees focussed on learners' perception of usefulness of the course on a 4 point Likert scale. From 2016–17 these questionnaires were updated to include pre and post course confidence scores in eight domains reflecting ENTS scored on a 3 point Likert scale. Student's t-test was used to calculate statistical significance between pre and post scores in Microsoft Excel. Qualitative statements on what attendees had learned and how it would impact practice were also collected. Results: We retrospectively analysed the questionnaire responses of 22 doctors, 21 nurses and two healthcare assistants. From 2012–16 weighted averages of responses across all 21 statements indicate acceptability of simulation as a technique for teaching ENTS (median number of respondents=38). From 2016–17 the average confidence across all eight domains increased (median number of respondents=16). Three of these achieved statistical significance (p<0.01) – 'I can manage an emergency clinical care scenario using time and resources efficiently', 'I can manage complaints effectively with positive outcomes' and 'I can understand the human factors that play a role in complex clinical care situations' (Chart 1). Qualitative statements of lessons learned indicated that attendees found debriefing with the actor giving a patient perspective a very informative experience, increasing patient centeredness and discovering useful strategies for future practice. Conclusions: Over the last 5 years, this course has attracted attendees within our own deanery and nationally. We have shown that a one-day ENTS simulation course is feasible and can have a significant impact on trainees' confidence in their non-technical skills. We believe this is a good model for delivering ENTS training for other centres to follow.